2010
DOI: 10.1186/1756-9966-29-155
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in the mitochondrial displacement loop and outcome of esophageal squamous cell carcinoma

Abstract: BackgroudAccumulation of single nucleotide polymorphisms (SNPs) in the displacement loop (D-loop) of mitochondrial DNA (mtDNA) has been described for different types of cancers and might be associated with cancer risk and disease outcome. We used a population-based series of esophageal squamous cell carcinoma (ESCC) patients for investigating the prediction power of SNPs in mitochondrial D-loop.MethodsThe D-loop region of mtDNA was sequenced for 60 ESCC patients recorded in the Fourth Hospital of Hebei Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 17 publications
0
27
2
Order By: Relevance
“…We have previously performed a number of studies on D-loop SNPs as predictive factors for digestive tract cancers (24,25,29). In the present study, for the first time, we suggest that, other than as predictors for cancer risk and outcome, SNPs in the D-loop are also predictors for age-at-onset in HCC patients.…”
Section: Of Cases (Years) -------------------------------------------mentioning
confidence: 53%
“…We have previously performed a number of studies on D-loop SNPs as predictive factors for digestive tract cancers (24,25,29). In the present study, for the first time, we suggest that, other than as predictors for cancer risk and outcome, SNPs in the D-loop are also predictors for age-at-onset in HCC patients.…”
Section: Of Cases (Years) -------------------------------------------mentioning
confidence: 53%
“…In our study, all the cancer risk-associated SNPs were identified in the HV segment region of the D-loop, with nucleotides 16293, 16298 and 16319 belonging to HV-Ⅰ, 262 to HV-Ⅱ and 488 to HV-Ⅲ. Cancer risk-and outcome-associated SNPs were identified in these regions in other types of cancer as well, including esophageal squamous cell carcinoma (17,27) and hepatocellular carcinoma (25,26). The HV segments are mutational hotspots at which germline and tumor mtDNA mutations preferentially occur (28).…”
Section: Discussionmentioning
confidence: 97%
“…An increase of mutations and SNPs in the mitochondrial D-loop region have been reported in a variety of cancers, including esophageal squamous cell carcinoma (17), hepatocellular carcinoma (18), oral squamous cell carcinoma (19) and lung cancer (20). In this case-control study, cancer risk-associated SNPs for RCC were investigated in a continuous sequence of mtDNA between nucleotides 16190 and 583, and 5 SNP sites, comprising 16293, 262, 488, 16298 and 16319, were identified.…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified cancer risk and outcome-associated SNPs of the D-loop in several types of cancer (25,26,30). In this study, selected SNPs in the mtDNA D-loop were examined for their ability to predict cancer outcome in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%